2009
DOI: 10.1007/s10643-009-0329-9
|View full text |Cite
|
Sign up to set email alerts
|

An Intergenerational Program with Benefits

Abstract: Illustrates how the director and teachers of a child care program and the staff of a residential nursing home facility collaborated to develop, implement, and evaluate an onsite intergenerational program. Describes program goals; recruitment plan; elder, staff, and teacher orientation; options for intergenerational activities; and program benefits. Article provides resources and suggestions for groups planning intergenerational programs. Preschool children (n = 38) who participated in the study were interviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 7 publications
2
28
0
Order By: Relevance
“…The finding of the study claimed that the children in both experimental conditions improved more in counting skills and quantity in comparison to children in the no-intervention control group. Despite the fact that former studies with older children (Holmes, 2009) had shown generalization effects on problem solving or in math, this study is the first one that has found generalization effects of working memory training on early numeracy in young children. In conclusion, the researchers claim that the advantage of this type of intervention is that it can easily be implemented in the regular kindergarten class, because it can be given in groups and does not require additional materials while the cooperation among the children is enhanced satisfactorily (Hornung et al, 2014).…”
Section: Support Children's Memory Skills In Mathsmentioning
confidence: 64%
“…The finding of the study claimed that the children in both experimental conditions improved more in counting skills and quantity in comparison to children in the no-intervention control group. Despite the fact that former studies with older children (Holmes, 2009) had shown generalization effects on problem solving or in math, this study is the first one that has found generalization effects of working memory training on early numeracy in young children. In conclusion, the researchers claim that the advantage of this type of intervention is that it can easily be implemented in the regular kindergarten class, because it can be given in groups and does not require additional materials while the cooperation among the children is enhanced satisfactorily (Hornung et al, 2014).…”
Section: Support Children's Memory Skills In Mathsmentioning
confidence: 64%
“…In the light of the above research, Holmes et al [45] compared the effects of cognitive training to stimulant medication on working memory impairments in children with ADHD. With Baddeley's [46] model of working memory as the underpinning for the assessments used in this study, they found that cognitive training improved verbal, visuo-spatial, and executive aspects of working memory alike.…”
Section: Support Pre-school Children With Working Memory Problems mentioning
confidence: 99%
“…Within the US, shared site intergenerational programmes have been running since at least the late 1970s, with for example, child care centres being co-located within nursing homes (Goyer & Zuses, 1998;Holmes 2009;Kaplan and Larkin 2004). Brownell (2008) described how high school students and care home residents living with dementia, participated in an organised arts programme.…”
Section: Intergenerational Connectivity and Practices In Care Homesmentioning
confidence: 99%